Automatic Peat Water Treatment Method with Electrocoagulation and Salt Addition Techniques to Improve Chemical Quality to Drinking Water - Hari Rudijanto Indro Wardono; Tri Cahyono; Nur Hilal; Kalasta Ayunda Putri (Universitas Negeri Semarang, 2022)
Abstrak. Good drinking water must meet the requirements of one of which is chemical parameters, namely iron. This research was conducted to support government programs in the development of the health sector and the achievement of MDGs targets, especially those related to improving drinking water treatment facilities and peat water treatment equipment that is easy to move. The study was conducted by a pre-experimental method, a one-group pretest-posttest approach. Sampling points are carried out in the initial reservoir and the final bath of the processing results. Replication is carried out three times at the use of voltages of 9 volts, 12 volts, and 15 volts. Manufacture of 4% saline solution as a coagulant material. Making artificial peat water with raw materials from Ngasinan village, Bawen District, Semarang Regency. Statistical analysis using the Anova test. Shows that used voltage of 9 volts on average can reduce iron levels by 100%, 12 volts by 90.80%, and at 15 volts by 90.57%. Complying with the requirements of the Minister of Health of the Republic of Indonesia Number 492 / Menkes / Per / IV / 2010 concerning Drinking Water Quality Requirements for iron content is 0.3 mg / lt. The difference in electrical voltage values does not have a significant effect on the decrease in iron content. It is necessary to make improvements to the research likes construction / position of the anode and cathode, the placement and protection of the sensor, tools used of the duration of sedimentation time (3 hours). using actual peat water, media cartridge for filtration.